Designing temperature-memory effects in semicrystalline polyurethane1. Issue 57 (25th June 2015) - Mirtschin, Nikolaus; Pretsch, Thorsten
<x xml:space="preserve">Abstract</x> Facile ways to design temperature-memory effects in semicrystalline polyurethane by thermomechanical programming are reported.